2017
DOI: 10.1111/ggi.13147
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical activity with a systolic blood pressure difference between arms in older people

Abstract: Aim: A increase in interarm systolic blood pressure difference (IASBPD) is believed to lead to increased risk of cardiovascular disease and to be a predictor of future cardiovascular events. The purpose of the present study was to test the hypothesis that an increased IASBPD is associated with reduced physical activity in older people. Methods:Older people who used a geriatric health services facility (n = 147, mean age 83.3 years) were enrolled. The prevalence of IASBPD in individuals with different levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies show that SAH and hypercholesterolemia are present in the majority of the old people population, and end up becoming one of the main causes for the development of other complications, whether or not it is associated with another disease. 23,[25][26][27] . SAH and high cholesterol can trigger cardiac, renal, peripheral and cerebral vascular impairment, leading to a hindered quality of life, resulting in the old person being unable to perform their activities due to neurological and motor complications 23,[25][26][27] , condition that explains the association found between NCDs, SAH, hypercholesterolemia and being bedridden.…”
Section: Continuation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that SAH and hypercholesterolemia are present in the majority of the old people population, and end up becoming one of the main causes for the development of other complications, whether or not it is associated with another disease. 23,[25][26][27] . SAH and high cholesterol can trigger cardiac, renal, peripheral and cerebral vascular impairment, leading to a hindered quality of life, resulting in the old person being unable to perform their activities due to neurological and motor complications 23,[25][26][27] , condition that explains the association found between NCDs, SAH, hypercholesterolemia and being bedridden.…”
Section: Continuation Ofmentioning
confidence: 99%
“…The cross-sectional research carried out with Japanese old people with the objective of testing the hypothesis that an increase in the difference in systolic blood pressure between the arms would be associated with a reduction in physical activity in old people, found that bedridden old people presented a difference in the systolic blood pressure between the arms in relation to walking and wheelchair-using old people 26 . Still, the bedridden lack of physical activity can be a predictive factor to raise blood pressure.…”
Section: Continuation Ofmentioning
confidence: 99%